2021
DOI: 10.1002/pc.26402
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural analysis and multi‐response optimization of mechanical properties of bulk molding compound

Abstract: In this article, the mechanical properties of commercial bulk molding compounds (BMC) based on the unsaturated polyester resin were maximized by optimizing glass fiber weight (FW) and fiber length (FL). An empirical design was utilized to study the influence of each parameter and its interaction on responses. Accordingly, three levels of FW (10, 15, and 20 wt.%) and FL (3, 6, and 12 mm) were used. A full factorial design was utilized to investigate the effect of each variable and their interaction on all respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…A desirability function‐based method comprises converting the predicted models of respond (y) into individual desirability functions (d). The alteration span of an individual desirability function is 0d1: Three states of desirability functions happen basis on result features [ 35 ] : Larger is better; Smaller is better; Nominal is better. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A desirability function‐based method comprises converting the predicted models of respond (y) into individual desirability functions (d). The alteration span of an individual desirability function is 0d1: Three states of desirability functions happen basis on result features [ 35 ] : Larger is better; Smaller is better; Nominal is better. …”
Section: Resultsmentioning
confidence: 99%
“…The R 2 (pred)-value is computed by orderly deleting each observation from the dataset, predicting the mathematical equation, and showing how well the model foresees the results for new observations. [35] Plus, the high R 2 (adj)-values (adjusted between 86.03% and 99.49%) and R 2 (pred)-values (adjusted between 78.83% and 99.23%) indicated that all models' predictabilities were well. The plots of normal probability investigated residuals are illustrated in Figure A1.…”
Section: Appendix: Statistical Analyses Amentioning
confidence: 98%
See 2 more Smart Citations
“…Adding fumed silica to the PP increased Young’s modulus, which was due to the high modulus of fumed silica. 31,32 Tensile strength is strongly dependent on the stress transfer between nanoparticles and the matrix. When good adhesion between the nanoparticles and the matrix is present, the applied stress is transferred from the matrix to the particles and improves the tensile strength.…”
Section: Resultsmentioning
confidence: 99%